CAM in the Production of Casting Patterns - Bílek, Ondřej; Rokyta, Luboš; Šimoník, Jaroslav (Manufacturing Technology Journal, 2012)
The article is focused on the production of permanent casting patterns from wood for impermanent moulds by the 5-axis machining centre. Programming of casting pattern was dealt with CAM software by two different manufacturers. Casting pattern, adapted by appropriate allowances, was loaded in the SolidCAM R10 and the CAM Express 7.5 by Siemens. Ergonomics in the working environment of programmes, operation verifications and theoretical machine time were compared. The casting pattern was machined after generating the NC code on FC3800 MACH milling machine. Monitored parameters during computer programming were associated with the measured values when machining casting pattern. Estimated parameters between the computer simulations differed minimally in general, although the programming methods of cutting operations were different. Considerable differences, as expected, were observed in the values of estimated and actual machine time.
Keywords: CAM; CNC Milling; Casting Pattern; Software